MAPPING OF CORRELATION AND DIVERSITY OF BODY LENGTH OF ETAWA CROSSBREED GOATS IN UMEJERO VILLAGE, BUSUNGBIU DISTRICT, BULELENG, BALI - Amirulah; I Putu Sampurna; Tjokorda Sari Nindhia (Buletin Veteriner Udayana, 2025)
Etawa Crossbreed (PE) goats are superior livestock with high adaptability and productivity. This study aims to analyze the correlation and diversity of body length measurements of PE goats in Umejero Village, Busungbiu District, Buleleng, Bali. 81 adult PE goats (aged 8-12 months) were measured for body length dimensions, including head, neck, body, tail, and horn lengths. The data were analyzed using descriptive methods and biplot analysis. The results showed that head length had the greatest diversity at 0.873%, followed by tail length at 0.778%, body length at 0.708%, horn length at 0.669%, and the most uniform neck length at 0.661%. A positive correlation was found between neck, horn, body, and tail lengths, while head length did not correlate with other dimensions.